Distribution of endemic Cicadas (Hemiptera: Cicadidae) on Evia and adjacent islands in Greece - Gogala, Matija (Acta entomologica slovenica (Ljubljana), 2014)
On the greek island of Evia (Euboea) we found and previously described three endemic species of Cicadettini: Cicadetta dirfica, Cicadetta hannekeae and Euboeana castaneivaga. Only one of them, C. hannekeae is present also in continental Greece. We tried to determine their geographical distribution on selected Aegean islands: Evia, Andros, Skopelos, Ikaria and Samos. Only on Andros we discovered one of the Evian endemics, E. castaneivaga, on other islands we did not detect any of the Evia endemic species mentioned above. We discuss the possible reasons for such limited distributions and are also providing data about other cicada species found on investigated islands.
Keywords: Cicadetta dirfica; Cicadetta hannekeae; Cicadidae; Euboeana castaneivaga; geografska razširjenost; geographical distribution; Grčija; Greece; Hemiptera; škržadi